2021
DOI: 10.2113/2021/1387282
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Plane Heterogeneity on Steam Flooding Development in Heavy Oil Reservoirs

Abstract: Steam flooding is proven to be an effective method to improve the development effect of heavy oil reservoirs. And steam flooding is the most common oil recovery technology for heavy oil reservoirs in China. However, because of the various reservoir physical properties, bring great challenges to successful steam flooding development. According to the previous research and development practice, we know that reservoir heterogeneity has a great influence on the development effect of water flooding. Due to the hete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
(31 reference statements)
0
1
0
Order By: Relevance
“…Figure 26 presents the production performance and the stage divisions during steam flooding. Qu et al 268 studied the influence of reservoir heterogeneity on steam flooding development results and found that permeability heterogeneity had the greatest influence, followed by thickness, and geometry had the least influence. Yu 269 reported that the steam injection dryness has a positive effect on the steam flooding effect.…”
Section: Microemulsion Floodingmentioning
confidence: 99%
“…Figure 26 presents the production performance and the stage divisions during steam flooding. Qu et al 268 studied the influence of reservoir heterogeneity on steam flooding development results and found that permeability heterogeneity had the greatest influence, followed by thickness, and geometry had the least influence. Yu 269 reported that the steam injection dryness has a positive effect on the steam flooding effect.…”
Section: Microemulsion Floodingmentioning
confidence: 99%